Toward a Comprehensive Understanding of Allergic Lung Disease - Corry, David B. (American Clinical and Climatological Association, 2009)
Allergic asthma is a respiratory disease induced by exposure to environmental agents that elicit allergic inflammation and transient airway obstruction and which produce the characteristic symptoms of cough and dyspnea. Prior to the advent of experimental models, asthma was believed to be caused primarily by the degranulation of mast cells and eosinophils primed by antigen-specific immunoglobulin E (IgE). More recent studies in mice have shown that T cells primarily mediate antigen-dependent airway obstruction and allergic inflammation through secretion of the cytokines interleukin 4 (IL- 4) and IL-13. Our additional studies indicate that a major environmental link to asthma may be through exposure to environmental proteinases and especially airway infection by proteinase-producing organisms such as fungi. Pending verification in humans, these findings suggest entirely new therapeutic interventions in asthma that include the restricted use of anti-inflammatory therapy and universal application of anti-fungal agents.